Microstructure and Mechanical Behaviour of ABOw Reinforced Aluminium Matrix Composite Synthesized by Powder Metallurgy route - Pandey, N.; Chakraborty, I.; Ram, S.C.; Majhi, M.R. (Institute of Physics Publishing, 2019)
In present study, the effect of Aluminum borate whiskers (ABOw) content (5, 10 and15 wt.%) on the development of Al-ABOw composite using powder metallurgy route has been investigated. Firstly, Aluminum borate whiskers (ABOw) were produced using sol-gel method. The commercial pure aluminum powder was used as matrix material in this investigation. Amongst, the various casting technology, the powder metallurgy route is most economical and extensively used by researchers. The microstructures of composites were observed using optical microscopy (OM), scanning electron microscopy (SEM). Transmission electron microscopy (TEM) analysis was performed for the observation of ABOw powder morphologies. The XRD analysis was carried out to confirm the phases and peak intensity of developed alloy and composites. The sintering was carried out at 600°C for all samples. After that, the bending test was carried out to calculate flexural strength of alloy and composites. The flexural strength 172-5 MPa was obtained maxima in composite with 10 wt.% ABOw along with improved hardness around 40.2HV. The result shows that, the composite exhibited better interfacial bonds, uniformity in microstructure and optimum flexural strength. © Published under licence by IOP Publishing Ltd.
Keywords: Powe Metallurgy; ABOw reinforcment